2012
DOI: 10.1002/hbm.22174
|View full text |Cite
|
Sign up to set email alerts
|

Linking novelty seeking and harm avoidance personality traits to cerebellar volumes

Abstract: Personality traits are multidimensional traits comprising cognitive, emotional, and behavioral characteristics, and a wide array of cerebral structures mediate individual variability. Differences in personality traits covary with brain morphometry in specific brain regions, and neuroimaging studies showed structural or functional abnormalities of cerebellum in subjects with personality disorders, suggesting a cerebellar role in affective processing and an effect on personality characteristics. To test the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 76 publications
(114 reference statements)
1
50
1
1
Order By: Relevance
“…Decreased gGMV with higher N scores has been reported in two studies (Jackson et al, 2011;Liu WY et al, 2013 -result restricted to females subgroup only). No significant gWMV variations with HA (Laricchiuta et al, 2014a), or with N (Jackson et al 2011 were detected, although a greater decline of gWMV with age in neurotics has been observed (Jackson et al, 2011). No significant associations between HA scores and volume of cerebral hempisheres volume was found, only in the males subgroup a negative HA -cerebellar cortex correlations (Laricchiuta et al 2014a).…”
Section: Global Gm/wm (Ggmv/gwmv) -Ne Traits Associationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Decreased gGMV with higher N scores has been reported in two studies (Jackson et al, 2011;Liu WY et al, 2013 -result restricted to females subgroup only). No significant gWMV variations with HA (Laricchiuta et al, 2014a), or with N (Jackson et al 2011 were detected, although a greater decline of gWMV with age in neurotics has been observed (Jackson et al, 2011). No significant associations between HA scores and volume of cerebral hempisheres volume was found, only in the males subgroup a negative HA -cerebellar cortex correlations (Laricchiuta et al 2014a).…”
Section: Global Gm/wm (Ggmv/gwmv) -Ne Traits Associationsmentioning
confidence: 79%
“…No significant gWMV variations with HA (Laricchiuta et al, 2014a), or with N (Jackson et al 2011 were detected, although a greater decline of gWMV with age in neurotics has been observed (Jackson et al, 2011). No significant associations between HA scores and volume of cerebral hempisheres volume was found, only in the males subgroup a negative HA -cerebellar cortex correlations (Laricchiuta et al 2014a). Knutson et al (2001) noticed a diminished ratio between the total brain volume and the remainder of the intracranial volume with N-Anxiety scores, as measured with NEO-PI-R.…”
Section: Global Gm/wm (Ggmv/gwmv) -Ne Traits Associationsmentioning
confidence: 79%
“…Esta dimensión, no sólo está constituida por la evaluación de la impulsividad, sino que incluye facetas como actividad exploratoria, extravagancia y planificación (Gutiérrez-Zotes et al,), lo que podría explicar esta más baja asociación. En comparación, la dimensión Evitación del Riesgo describe a los sujetos con mayor inhibición conductual, aburrimiento y pesimismo, considerándose más ansiosos y menos impulsivos, lo que va en consonancia con nuestros resultados y con los estudios que describen que sujetos sanos con un patrón conductual de Búsqueda de Novedad obtienen puntuaciones opuestas en Evitación del Riesgo (Laricchiuta et al, 2014).…”
Section: Discussionunclassified
“…All participants were right-handed as assessed with the Edinburgh Handedness Inventory (Oldfield, 1971). Seventy-five out of the 100 subjects had also been included in our previous study (Laricchiuta et al, 2012), while 25 new subjects were added. Out of 125 subjects of the previous study, fifty participants were not included in the present research since their DTI images exhibited bad coverage and venetian blind artifacts at the level of the cerebellum.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, by using a Region of Interest (ROI)-based approach, in a large sample of healthy subjects we reported WM and GM cerebellar volumes associated positively with NS and negatively with HA (Laricchiuta et al, 2012), while no significant association was found between cerebellar volumes and RD and P scores.…”
Section: Introductionmentioning
confidence: 99%